Analisis Dampak Pengembangan Pariwisata Terhadap Perekonomian Masyarakat Lokal di Era New Normal - Priska Nurul Hazanah Putri; Sri Astuti; Camelia Safitri (Jurnal EMT KITA, 2022)
Tourism is able to raise the level of the economy, but reflecting it on the Covid-19 pandemic, and its transition to the New Normal Era continues to be debated. Thus, this study aims to analyze the impact of tourism development on the economy of local communities in the new normal era. This study uses a phenomenological qualitative method. The sample came from the people of Tidung Island, the sample was selected using a purposive sampling technique. Collecting data with interview instruments, focus group discussions, document studies, and observation. Check the validity and reliability of the data using triangulation techniques. The data analysis is Interactive Model Analysis. The results show that the implications of new normal era tourism development are confirmed to have a positive impact on the economy and welfare of local communities.